Analyzing the Impact of Governance, Environment and Trade on Inward FDI: A Case of Cambodia, Thailand and Vietnam from ASEAN - Farrukh Nawaz Kayani; Ismat Nasim; Khalil Abu Saleem (International Journal of Energy Economics and Policy, 2024)
The purpose of the study is to analyze the empirical link between governance, environmental quality, and trade as it relates to foreign direct investment in Cambodia, Thailand, and Vietnam for the period ranging from 1996 to 2022. Mixed order of integration (0 and 1) was discovered after applying four panel unit tests (IPS-W stat, ADF- Fisher, PP-Fisher, and LLC t). The Kao Residual Co-integration test was carried out to determine whether there was co-integration among the variables of the study. The results of the test demonstrated that some variables are, in fact, co-integrated during the investigation. The findings of unit root tests reveal the use of Panel ARDL, and the results demonstrate that governance has a positive overall effect on FDI. This is because tightening the control of corruption, improving regulatory quality, and strengthening the rule of law are all contributing to an increase in FDI in Cambodia, Thailand, and Vietnam. The study concluded that there is a link between a negative opinion of the efficacy of the government and foreign direct investment; however, this association did not reach the level of statistical significance required to be considered significant. To encourage FDI, trade also provides access to natural resources as the free flow of raw materials and intermediate goods is being supported by the initiatives connected to the promotion of FDI, which is made possible through trade.